Evaluation of surveillance respiratory culture in predicting nosocomial pneumonia pathogens - Tajudin, Syazwani Mohd (2020)
Ventilator-associated pneumonia (VAP) is a significant cause of morbidity and mortality for patients who are managed in Intensive Care Unit (ICU). It is the leading cause of prolonged hospital stay, infection with multidrug-resistant organisms and increased hospital cost. Surveillance respiratory cultures are routinely done despite the absence of clinical evidence for an infection. The value of the surveillance respiratory cultures to predict the causative organism is still uncertain and debatable. To evaluate the clinical value of respiratory culture surveillance in predicting the causative agents for VAP in ICU patients. This was a prospective observational study which was carried out in the General ICU of Hospital Universiti Sains Malaysia, between July 2017 to December 2018. All adults’ patients who were taken surveillance respiratory were included in the study. Patients were followed up till they were transferred out from the ICU. Results of respiratory culture for surveillance and diagnostic were reviewed and analysed using Cohen's kappa coefficient (κ). A total of 193 patients were included in this study. 88/193 (46%) patients had positive surveillance cultures with a total of 108 isolates. Out of 63/193 (32.6%) patients had subsequent respiratory cultures, 45/63 (71.4%) patients fulfilled the research criteria for VAP. Only 35/45 (78%) had positive diagnostic cultures. The most common microorganism isolated from surveillance respiratory cultures was Klebsiella pneumoniae (33/108, 30.5%). The other microorganisms were Staphylococcus aureus (22/108, 20.3%), Pseudomonas aeruginosa (11/108, 10.2%), Enterobacter species (10/108, 9.2%), and Acinetobacter species (8/108, 7.4%). The most common microorganism isolated from diagnostic cultures was Acinetobacter species (16/53, 30%). The other microorganisms were Pseudomonas aeruginosa (12/53, 22.6%), and Klebsiella pneumoniae (11/53, 20.7%). The level of agreement between surveillance and diagnostic culture using Cohen’s kappa coefficient show only fair agreement, 0.229 (according to the number of VAP cases n=45) and slight agreement, 0.168 when calculated according to the number of isolates (n=66). Gram-negative bacteria were the most common microorganism isolated in both surveillance and diagnostic culture. Surveillance respiratory cultures had limited value in predicting the causative agents of VAP. Diagnostic culture taken on suspicion or onset of VAP remained as the gold standard for the diagnosis.